The Virulence Factor p25 of Beet Necrotic Yellow Vein Virus Interacts With Multiple Aux/IAA Proteins From Beta vulgaris: Implications for Rhizomania Development - Muellender, Maximilian M.; Savenkov, Eugene I.; Reichelt, Michael; Varrelmann, Mark; Liebe, Sebastian (Frontiers in Microbiology, 2022)
Rhizomania caused by Beet necrotic yellow vein virus (BNYVV) is characterized by excessive lateral root (LR) formation. Auxin-mediated degradation of Aux/IAA transcriptional repressors stimulates gene regulatory networks leading to LR organogenesis and involves several Aux/IAA proteins acting at distinctive stages of LR development. Previously, we showed that BNYVV p25 virulence factor interacts with BvIAA28 acting at early stages of LR initiation. The evidence suggested that p25 inhibits BvIAA28 nuclear localization, thus, de-repressing transcriptional network leading to LR initiation. However, it was not clear whether p25 interacts with other Aux/IAA proteins. Here, by adopting bioinformatics, in vitro and in vivo protein interaction approaches we show that p25 interacts also with BvIAA2 and BvIAA6. Moreover, we confirmed that the BNYVV infection is, indeed, accompanied by an elevated auxin level in the infected LRs. Nevertheless, expression levels of BvIAA2 and BvIAA6 remained unchanged upon BNYVV infection. Mutational analysis indicated that interaction of p25 with either BvIAA2 or BvIAA6 requires full-length proteins as even single amino acid residue substitutions abolished the interactions. Compared to p25-BvIAA28 interaction that leads to redistribution of BvIAA28 into cytoplasm, both BvIAA2 and BvIAA6 remained confined into the nucleus regardless of the presence of p25 suggesting their stabilization though p25 interaction. Overexpression of p25-interacting partners (BvIAA2, BvIAA6 and BvIAA28) in Nicotiana benthamiana induced an auxin-insensitive phenotype characterized by plant dwarfism and dramatically reduced LR development. Thus, our work reveals a distinct class of transcriptional repressors targeted by p25.